Sinwattana: Raising capital through crowdfunding - CHIYACHANTANA, Chiraphol N. (Institutional Knowledge at Singapore Management University, 2021)
In January 2021, Kwek Hong Sin, a Singaporean, attended a crowdfunding roadshow. She had been captivated by Thailand’s retail environment and founded the crowdfunding platform Sinwattana in 2012 to help Thai businesses, particularly SMEs, raise capital. SMEs constituted over 99% of all enterprises in Thailand, and many were unable to borrow from banks because of strict lending requirements. These businesses suffered from the lack of government support, limited marketing skills and inadequate skilled labour. However, Kwek felt that Thai businesses were worth investing in. Crowdfunding would allow them to issue debt or equity directly to individual investors, including those overseas. Sinwattana provides consultation services to help companies succeed, and also offers business insights to prospective investors. The Sinwattana platform allows these stakeholders to connect; it provides companies with much needed capital and investors with attractive returns they might not have access to elsewhere. The case can be used in courses on Finance, Financial Equity Analysis and Portfolio Management, Technology and Innovation, and Strategy, as well as sessions on FinTech and financial inclusion. Through the lens of Sinwattana, the case exposes students to a burgeoning area within FinTech and gives them an understanding of how crowdfunding platform works. Students will learn to identify potential growth opportunities for an innovative financial service and leverage that understanding to build a competitive advantage by carefully considering what the target market values and how to deliver it better. The case also teaches students to think critically about identifying competition and target markets.